Investigating the Impact of a Multiple Choice Questions Standardization Workshop on the Performance and Satisfaction of Nursing and Midwifery Faculty Members for Designing the Final Examination Questions and Student Satisfaction in Zanjan University of Medical Sciences - Azam Maleki (Zanjan University of Medical Sciences and Health Services, 2020)
Background & Objective: Designing standard Multiple-Choice Questions (MCQs) can enhance education quality. This study aimed to determine the effect of holding a workshop on the standardization of MCQs for the final examination of the performance and satisfaction of faculties and student satisfaction in the Zanjan University of Medical Sciences. Materials and Methods: This was a pre-post single-group interventional study performed during 2018-2019. The performance of the faculties was assessed in terms of observing the structural rules and taxonomic level of the questions in the two stages before the consecutive semesters after the intervention. In addition, the level of satisfaction was evaluated using a researcher-made questionnaire. The sample population consisted of 50 faculty members selected by a simple random method. The educational content was composed of the objective questions design principles, face and content validity, and difficulty/discrimination indices of the questions. Moreover, data analysis was performed applying descriptive statistics and chi-square at 95% confidence interval. Results: This study reviewed 932 and 1679 questions before and after the intervention, respectively. There was a higher satisfaction level for all the Millman checklist criteria after intervening in the structure of questions. As a result, the total mean score of the structure of the questions increased from 12.67±0.86 to 13.0±06.69, demonstrating a statistically significant increase in this regard (P≤0.001). The comprehension and knowledge questions had the highest, and evaluation questions had the lowest percentage per Bloom's taxonomy in each semester. The satisfaction level of the tutors